2021
DOI: 10.1093/cid/ciab123
|View full text |Cite
|
Sign up to set email alerts
|

Coronavirus disease 2019 (COVID-19) Versus Influenza in Hospitalized Adult Patients in the United States: Differences in Demographic and Severity Indicators

Abstract: Background Novel coronavirus disease 2019 (COVID-19) is frequently compared with influenza. The Hospitalized Adult Influenza Vaccine Effectiveness Network (HAIVEN) conducts studies on the etiology and characteristics of U.S. hospitalized adults with influenza. It began enrolling patients with COVID-19 hospitalizations in March 2020. Patients with influenza were compared with those with COVID-19 in the first months of the U.S. epidemic. Methods… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
30
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 23 publications
(38 citation statements)
references
References 30 publications
(21 reference statements)
7
30
1
Order By: Relevance
“…Our findings differ from a study in critically ill adults hospitalized with influenza or COVID-19 across 2 academic centers that reported COVID-19 to be associated with worse respiratory outcomes [ 23 ]. Another study of hospitalized adults [ 24 ] reported patients with COVID-19 to have fewer underlying conditions, increased need for ICU care and mechanical ventilation, and much higher mortality than those with influenza infection. Similar to that adult study, we showed that adolescents (aged 13–17 years) and preschoolers (aged 24–59 months) had longer hospital and ICU stays with COVID-19 than with influenza.…”
Section: Discussionmentioning
confidence: 99%
“…Our findings differ from a study in critically ill adults hospitalized with influenza or COVID-19 across 2 academic centers that reported COVID-19 to be associated with worse respiratory outcomes [ 23 ]. Another study of hospitalized adults [ 24 ] reported patients with COVID-19 to have fewer underlying conditions, increased need for ICU care and mechanical ventilation, and much higher mortality than those with influenza infection. Similar to that adult study, we showed that adolescents (aged 13–17 years) and preschoolers (aged 24–59 months) had longer hospital and ICU stays with COVID-19 than with influenza.…”
Section: Discussionmentioning
confidence: 99%
“…Lastly, COVID-19 patients were found to have significantly worse outcomes than influenza patients: More often transferred to intensive care unit with a higher rate of mortality [13]. The severity of COVID-19 compared to influenza was demonstrated again in a study by Talbot et al, where patients with COVID-19 showed greater severity and complications, including more ICU admissions (aOR 5.3, 95% , ventilator use (aOR 15.6, 95% CI 10.7-22.8), seven additional days of hospital stay in those discharged alive, and death during hospitalization (aOR 19.8, 95% CI-12.0, 32.7) [14].…”
Section: Discussionmentioning
confidence: 86%
“…Regarding the outcome, both infectious agents can lead to ARDS and death. Although affected by the timing and by the region (the quality of the care offered varies according to the phase of the pandemic, the “preparedness” of the health system and the economic level of the country), COVID-19 showed higher mortality or worse outcomes than Influenza in adulthood 26 , 28 , 31 33 …”
Section: Discussionmentioning
confidence: 99%